Potensi Mewujudkan Pondok Pesantren Mahasiswa di Perguruan Tinggi Universitas Jambi Sebagai Penguatan Karakter dan Visi Pendidikan Bangsa - K.A. Rahman; Agung Yusup; Firman Afrian Pratama; Mulyadi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
In the era of Globalization and Digitalization, it is now easier to spread information, especially religious values. Religious values are integrated in the world of education. There are so many Islamic religious sects spread across Indonesia. However, not all religious sects are recognized for their sanad and the validity of their knowledge. A lot of information about the Islamic religion that is spread cannot be recognized as true because of the lack of reference sources for knowledge and the quality of human resources for teaching staff. Likewise, not all elements of education have a valid (sahih) source of religious knowledge, and not many outputs from education have basic religious values, namely having noble morals. The attitudes, ethics, character and morals of students, especially students at university level, still pay little attention to it. All components only focus on the content and learning values in the form of numbers, without prioritizing educational goals that prioritize morals. As the Messenger of Allah said.